2000
DOI: 10.1007/s002849910018
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin and Amoxicillin Susceptibility of Helicobacter pylori Strains Isolated from Adult Patients with Gastric or Duodenal Ulcer in Italy

Abstract: Helicobacter pylori strains, isolated from 100 gastric biopsies from 49 previously untreated adult patients with endoscopy and histology-confirmed gastric or duodenal ulcer, were tested for in vitro antimicrobial susceptibility. Strains were isolated from biopsies of 75.5% (37 of 49) patients before therapy and of 13.5% after therapy. Clarithromycin and amoxicillin susceptibility testing was performed on pretreatment and posttreatment strains by using the agar disk diffusion method and E-test, a quantitative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…The isolation rate of H. pylori among dyspeptic patients by culture and rapid urease test was inconsistence with Franzin et al 16 who reported that 75.5% of dyspeptic patients were H. pylori positive. On the other hand, our findings were higher than the percentage in the study obtained by Matsukura et al 12 Studies performed at Ismailia (Egypt), 66% and 68%, respectively of dyspeptic patients were H. pylori positive.…”
Section: Discussionmentioning
confidence: 88%
“…The isolation rate of H. pylori among dyspeptic patients by culture and rapid urease test was inconsistence with Franzin et al 16 who reported that 75.5% of dyspeptic patients were H. pylori positive. On the other hand, our findings were higher than the percentage in the study obtained by Matsukura et al 12 Studies performed at Ismailia (Egypt), 66% and 68%, respectively of dyspeptic patients were H. pylori positive.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, somewhat more reassuring figures have emerged from studies conducted in northern Italy. Primary resistance to CLA was documented in only 1.8% of the H. pylori isolates recovered in the Northeast [33] and in 8.8% of those examined in a northwestern region of the country [34]. Figures from different areas of the world obviously vary widely: relatively low or moderate rates have also been reported in Lebanon (4%) and in Israel (8%) [19,20], while in North America [18], Europe [10,11,17], and Asia [14,15], resistance has been observed in up to 12, 15 and 13% of isolates, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical combination of a proton pump inhibitor and antimicrobial agents such as clarithromycin or metronidazole is the most favoured treatment (Franzin et al, 2000;Megraud, 2004). However, the increasing use of these antibiotics causes the development of clinical isolates of H. pylori resistant to commonly used antibiotics.…”
Section: Introductionmentioning
confidence: 99%